Variabilitas Suhu di Samudera India Pada Saat Indian Ocean Dipole Positif Tahun 2006 - Septi Johan (JURNAL ENGGANO, 2025)
The Indian Ocean Dipole (IOD) is a phenomenon of ocean and atmosphere interaction characterized by differences in sea surface temperature between the eastern (90oE-110oE and 10oS-0oN) and western (50oE-70oE and 10oS-10oN) of Indian Ocean. This study examines the variability of the temperature of the Indian Ocean during the positive evolution of the Indian Ocean Dipole (IOD) in 2006. The data used in this research are Sea Surface Temperature (SST) data, wind data, monthly Sea Surface Height (SSH) data and current velocity data. zonal. These data were then analyzed using a low-pass filter with a 13-month cut-off period to observe the IOD phenomenon. The results of this study indicate that positive IOD evolution in 2006 was identified through the IOD Index, this is also supported by the results of temperature data analysis. Based on temperature data, there is a pattern of temperature differences between the eastern and western regions of the Indian Ocean. In May, the surface temperature begins to decrease, indicating the start of the IOD evolutionary phase. IOD began to occur in May with a temperature of -0.5oC. Over time, IOD evolution reaches a peak in September-October with a temperature of -1.8oC and begins to experience evolutionary decay in November-December with a temperature of -0.2oC. IOD evolution that occurs on the surface is influenced by zone currents and surface wind movements that move to the left. The positive IOD movement to the west also affects the decrease in sea level in the west coast of Sumatra which is marked by a negative value of SSHA.   Keywords: Indian Ocean Dipole, Lowpass Filter, Temperature